A new controller design method for an electric power steering system based on a target steering torque feedback controller. (January 2021) - Lee, Dongwook; Jang, Byeonggwan; Han, Minwoo; Kim, Kyung-Soo
Abstract: This paper describes a novel electric power steering (EPS) system controller that distinguishes the steering feel design problem from the system stability and control performance problem and provides a design methodology for each problem. The suggested controller, called the target steering torque feedback controller, consists of two modules: the steering feel generation logic module defines the target steering torque that the driver should feel under a given driving condition, and the steering torque feedback controller module controls the assist motor so that the driver actually feels the defined target torque. By disassociating all nonlinear elements related to steering feel tuning from the feedback controller, the inherent difficulties of the conventional EPS controller in terms of the coupling of system stability analysis and steering feel design are overcome. Rack-force-based steering feel generation logic that creates a familiar steering feel for drivers while transmitting the road condition information is suggested and design criteria of the steering torque feedback controller in the frequency domain are proposed to ensure robust stability, tracking performance and noise attenuation. In addition, a disturbance observer is applied to the feedback controller to compensate for the effect of disturbances and to improve tracking performance. The proposed controller design method is verified by conducting computer simulations and a vehicle test. Highlights: Limitations of the conventional electric power steering controller structure are addressed. A novel electric power steering controller separating the steering feel design and system stability/performance problem. Steering feel generation logic determines the target torque that should be felt by the driver at that moment. A steering torque feedback controller controls the assist motor for the driver to feel the desired target torque. Design method for the proposed controller is suggested and verified through simulation and vehicle test.